Brand’s Responses to the Covid-19 Pandemic - Mitrović, Ksenija; Novaković, Nebojša; Spajić, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
To maintain relevance in the face of the new normality, companies are considering new approaches to engage their consumers. Brands are facing the challenge of reacting quickly and adapting their activities to consumer expectations. The unavailability of brands due to disruptions in the supply chain, but also the endangered loyalty require finding new opportunities and activities that will maintain the connection with consumers. The paper presents the responses of brands and their adaptation to the conditions caused by the global covid-19 pandemic, followed by examples. The brand response most often involved encouraging people to act or adopt a state that reflects consideration and empathy, and social responsibility was the focus. In addition to the successful ones, there were also campaigns that were considered to be unacceptable. From the earliest responses involving withdrawal, activities have changed to gain (and maintain) a competitive basis. The reaction of brands implied a change in the tone of communication, special efforts towards building an emotional connection with consumers and strengthening social engagement. The paper provides an overview of brand behavior in times of crisis, when the value of digital experiences increases.